Reducing Labor Intensity in the Development of New Universal Cutting Fluids for Machining - Popov, Alexey; Krasnikova, Iuliia (Manufacturing Technology Journal, 2018)
The process of developing new universal cutting fluids is labor-intensive due to the requirement of conducting experiments to determine the impact of numerous additives on tool life during different technological operations. Therefore, finding the best cutting fluid, the use of which will result in the longest tool life, is a long and laborious process. To reduce labor intensity while creating new cutting fluids accelerated methods are applied first, such as the method of determining the tribometric properties of a new fluid. Subsequently wear tests are carried out, using only those cutting fluids which show the best tribological behavior.The aim of this study is to reduce labor intensity in developing new universal cutting fluids. For this purpose, a new accelerated method has been developed, which helps to determine the capability of the fluid to counteract the adhesion between the chips and the cutting tool. Furthermore, a new sequence of cutting fluid tests has been proposed which significantly reduces the amount of wear tests, resulting inconsiderable reduction of the overall labor intensity in the development of new cutting fluids.
Keywords: Adhesion; Cutting fluid; Machining; Wear